RANCANG BANGUN SISTEM INFORMASI PEMESANAN WEDDING ORGANIZER BERBASIS ANDROID (STUDI KASUS: KOTA PEKANBARU) - Sugeng Purwantoro Edy Suranta G.S; Melisa Adhari (Jurnal Komputer Terapan, 2022)
Wedding Organizer is a service that helps in the preparation and implementation of a wedding party. In this system, users can choose concepts to use such as aisles and decorations, wedding dresses, make-up, documentation, catering, and entertainment. This application is using android platform and build with the prototyping method. The result of this research is users can place an order for a wedding organizer via online. Based on functionality testing, the application that has been built runs as expected. Meanwhile, based on the questionnaire testing of the respondents, it was found that 70.68% agreed that this application was useful. And based on the results of usability testing, it was found that 72.0% of respondents agreed that the application was useful or usefulness, 78.0% of respondents agreed that the system was easy to use or ease of use, then 81.3% of respondents agreed the system was easy to learn, and 74.0% of respondents agree the resulting application is satisfactory and in accordance with expectations or satisfaction